Edukasi Pengelolaan Sampah Rumah Tangga Di Desa Tonjung, Bangkalan - Eka Suci Daniyanti, Eka; Eddy Moeljono1 (ABDIMAS Madani, 2025)
The amount of household waste production is increasing, resulting in a negative impact on the environment and public health if it is not handled properly immediately. The impact of less-than-optimal waste management is the occurrence of various environmental problems including poor environmental sanitation, the emergence of various types of diseases due to flooding the organic content of agricultural land and global warming are problems that arise from waste. The aim of this community service activity is to provide information to the community in the Tonjung area, Bangkalan on managing household waste appropriately. Implementation of community service activities is divided into several sessions, namely pre-test, material delivery, and post-test. There is an increase in information about appropriate and correct waste management after being given education through materials and videos about proper waste management. Education to the community can provide a stimulus to the community itself to achieve health, starting from managing household waste appropriately, so that it is hoped that there will be changes in healthy behavior in the community.